Political Education As A Foundation For Development: Educational Systems, Strategies And Techniques - Eri Deka Gustiar; Kasful Anwar US; As'ad Isma (International Journal of Education, Vocational and Social Science, 2023)
This study aims to analyze and describe: 1) influence politics in the National Education System in Indonesia and 2) political influence towards the curriculum in the National Education System . This research is qualitative research with a literature study approach. Data is collected via document study. Data were analyzed using interactive model analysis. Results this study shows that 1) Politics in the National Education System in Indonesia has influence on the education budget and educational resources. In addition, politics also influences curriculum changes. Based on The historical chronology of the national education curriculum has changed curriculum from 1947 to 20 22 . Changes to the curriculum it happened when there was a change in political conditions in Indonesia. Change politics was followed by changes in curriculum policies in the national education system. This shows that there is influence politics with the national education system that is identified with the presence Curriculum change in Indonesia. 2) The influence of politics on the curriculum in the actual national education system is the elimination of some subjects, reducing and merging subject matter with goals educational efficiency and effectiveness